2007
DOI: 10.1136/oem.2005.021170
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for hand-wrist disorders in repetitive work

Abstract: Objectives: To identify the risk of hand-wrist disorders related to repetitive movements, use of hand force and wrist position in repetitive monotonous work. Methods: Using questionnaires and physical examinations, the prevalence and incidence of hand-wrist pain and possible extensor tendonitis (wrist pain and palpation tenderness) were determined in 3123 employees in 19 industrial settings. With the use of questionnaires and video recordings of homogenous work tasks number of wrist movements, hand force requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
42
1
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 27 publications
6
42
1
3
Order By: Relevance
“…Exposure to workpace dependent on the technical organization, which could represent a measure of the repetitiveness of the task, increased the risk of DQD. This agrees with previous studies on hand-wrist tendonitis (12,13,16,31,34,35). The multifactorial nature of disorders involving several biomechanical and organizational factors is coherent with the literature reporting higher risk of hand-wrist tendinitis for combined exposure to work-related risk factors (13,32).…”
Section: Petit Le Manac'h Et Alsupporting
confidence: 82%
See 1 more Smart Citation
“…Exposure to workpace dependent on the technical organization, which could represent a measure of the repetitiveness of the task, increased the risk of DQD. This agrees with previous studies on hand-wrist tendonitis (12,13,16,31,34,35). The multifactorial nature of disorders involving several biomechanical and organizational factors is coherent with the literature reporting higher risk of hand-wrist tendinitis for combined exposure to work-related risk factors (13,32).…”
Section: Petit Le Manac'h Et Alsupporting
confidence: 82%
“…The multifactorial nature of disorders involving several biomechanical and organizational factors is coherent with the literature reporting higher risk of hand-wrist tendinitis for combined exposure to work-related risk factors (13,32). Contrary to some studies, no association was found for the physical demands of the task, forceful exertion (12,13,31,34,35) or exposure to hand-wrist vibrations (31). DQD was not associated with computer use in our study, although a high incidence of DQD has been reported in a large cohort of computer users (36).…”
Section: Petit Le Manac'h Et Alsupporting
confidence: 47%
“…The findings of the current study are constant with other studies that found low social support were related to increased risk of neck, shoulder, and upper-back pain [39]. Furthermore, previous studies proved that workers with elbow and shoulder disorders worked reduced hours of their working time [40].…”
Section: Discussionsupporting
confidence: 78%
“…Using objective measurements, our studies constitute an important contribution to the investigation of the association between work-related forward bending and LBPi because previous studies have mainly relied on self-reported measures (11). Furthermore, this study is -to our knowledge -among the first using long-term objective measurements of forward bending during longer time periods, circumventing drawbacks due to selected time windows and short recording periods (18)(19)(20)(21).…”
Section: Discussionmentioning
confidence: 97%
“…One reason for the conflicting results can be differences in methodology used to measure forward bending of the trunk (15). The majority of studies investigating the association between forward bending of the trunk and LBP (11) have been criticized for using self-reported measures (16,17) or the short window of observations (18)(19)(20)(21). Therefore, valid objective measurements using accelerometers are preferable due to higher precision (22) and possibility for longer measurement periods (23).…”
Section: Social Support At Work Forward Bending and Low-back Painmentioning
confidence: 99%